Die Bedeutung des sportmechanischen Belastungsprofils im Leistungshockey für die thorakolumbale Wirbelsäulenform - Dalichau, S.; Scheele, K. (Sport-Orthopädie - Sport-Traumatologie, 2002)
In order to be able to assess the influence of the sporting mechanical stress profile on the thoraco-lumbar spinal column shape during competitive hockey the spinal curvature (C7-S2) in three dimensions was determined for 71 active male hockey players aged 25.3 ± 4.1 years with a sporting exposure of 13.4 ± 2.9 years and 1347 non-athletes and hobby athletes of the same sex and age group, by means of non-invasive ultrasonic touch rod procedure. While there were no significant differences from the control group (CG) for the sagittal projection, it was possible to detect statistically significant changes for the hockey players in the case of the frontal and transversal planes. The criteria investigated, shoulder-pelvic tilt, lateral inclination and lateral shape deviation, were directed to the right side in the hockey group, independent of arm dominance. In contrast the shoulder-pelvic rotation exhibited a shoulder axis that was markedly rotated to the left for both left- and right-handers.